Willingness of people with mental health disabilities to travel in driverless vehicles. (March 2019) - Bennett, Roger; Vijaygopal, Rohini; Kottasz, Rita
Abstract: Introduction: The purpose of the research was to examine possible barriers to the use of autonomous vehicles (AVs) perceived by people with intellectual disabilities. Access to user-friendly and equitable transportation is a major factor influencing the health and well-being of people with mental disabilities, and AVs have much to offer to intellectually vulnerable travellers. It is important therefore to determine the factors that will encourage mentally disabled people to travel in driverless vehicles. Methods: A Structural Topic Modelling (STM) approach was employed to analyse 177 responses of mentally disabled people to an open-ended question concerning their willingness to travel in an AV. Outcomes to the STM, together with data on the sample members' levels of internal locus of control, generalised anxiety, age, gender, prior knowledge of AVs, and the intensity of an individual's disability were then incorporated into a structural equation model constructed to relate attitudinal topics identified by the STM to the participants' willingness to travel in AVs. Results: Three categories of attitude towards AVs arose from the STM; respectively involving freedom, fear and curiosity. Two of the three attitudinal topics, freedom and fear, significantly predicted the participants' willingness to use driverless vehicles. The "freedom" topic was significantly explained by generalised anxiety, intensity of disability, and prior knowledge of AVs. Topic two ("fear") depended significantly on generalised anxiety and prior knowledge, and also on locus of control and (female) gender. The third topic ("curiosity") was influenced by locus of control and prior knowledge. Conclusion: The results of the study offer a template for government agencies and vehicle manufacturers to apply when formulating public information campaigns promoting the acceptance of driverless vehicles by intellectually disabled people. Public information campaigns targeted at this important segment of the population should incorporate messages based on factors known to affect mentally disabled people's attitudes towards autonomous vehicles. Highlights: Examines intellectually impaired people's concerns regarding autonomous vehicles. Applies a semi-automated qualitative research method. Suggests antecedents and consequences of mentally disabled people's attitudes towards AVs. Identifies main points for inclusion in public information campaigns. Argues for consideration of mentally disabled people's views when creating AV transportation policies.